2011
DOI: 10.2903/j.efsa.2011.2178
|View full text |Cite
|
Sign up to set email alerts
|

Scientific Opinion on Flavouring Group Evaluation 78, Revision 1 (FGE.78Rev1): Consideration of aliphatic and alicyclic and aromatic hydrocarbons evaluated by JECFA (63rd meeting) structurally related to aliphatic and aromatic hydrocarbons evaluated by EF

Abstract: The Panel on Food Contact Materials, Enzymes, Flavourings and Processing Aids of the European Food Safety Authority was requested to consider evaluations of flavouring substances assessed since 2000 by the Joint FAO/WHO Expert Committee on Food Additives (the JECFA), and to decide whether further evaluation is necessary, as laid down in Commission Regulation (EC) No 1565/2000. The present consideration concerns a group of 24 aliphatic, alicyclic and aromatic hydrocarbons evaluated by the JECFA (65th meeting). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…The other products contained limonene in quantities below or in the range of MSDI USA. The level of alpha-pinene present in H60376 (14 mg for 3 g ingested) was 6 times above the MSDI-EU limit of 2.2 mg/pers/day cited by EFSA, calculated for a person of 60 kg [32]. Beta-pinene was detected in H60376 at levels corresponding to a daily intake more than 100 times above the MSDI USA limit of 760 µg/pers/day (MSDI EU of 1.3 mg/pers/day) [32], indicating a potential risk from oral chronic exposure.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…The other products contained limonene in quantities below or in the range of MSDI USA. The level of alpha-pinene present in H60376 (14 mg for 3 g ingested) was 6 times above the MSDI-EU limit of 2.2 mg/pers/day cited by EFSA, calculated for a person of 60 kg [32]. Beta-pinene was detected in H60376 at levels corresponding to a daily intake more than 100 times above the MSDI USA limit of 760 µg/pers/day (MSDI EU of 1.3 mg/pers/day) [32], indicating a potential risk from oral chronic exposure.…”
Section: Discussionmentioning
confidence: 97%
“…The level of alpha-pinene present in H60376 (14 mg for 3 g ingested) was 6 times above the MSDI-EU limit of 2.2 mg/pers/day cited by EFSA, calculated for a person of 60 kg [32]. Beta-pinene was detected in H60376 at levels corresponding to a daily intake more than 100 times above the MSDI USA limit of 760 µg/pers/day (MSDI EU of 1.3 mg/pers/day) [32], indicating a potential risk from oral chronic exposure. Gamma-terpinene was also found in H60376 at levels leading to a total daily intake more than 100 times above the MSDI USA level of 321 µg/pers/day [32].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In contrast, the susceptibility of different strains of rats to renal carcinogenicity varies widely (27), with Bastaki et al, finding a lack of renal toxicity to β-myrcene when using Sprague-Dawley rats. In addition, the B6C3F1 male mice included in the NTP study are recognised for having a high and variable background incidence of hepatocellular tumours; on this basis the EFSA has rejected its relevance for human health (144). Furthermore, based on this review, numerous studies have indicated the anti-mutagenic and anti-metastatic effects of β-myrcene on several different cancer cell lines (25,145), highlighting the positive effects of β-myrcene on cancer prevention.…”
Section: Discussionmentioning
confidence: 99%